2014
DOI: 10.1021/es5002715
|View full text |Cite
|
Sign up to set email alerts
|

Emissions and Climate-Relevant Optical Properties of Pollutants Emitted from a Three-Stone Fire and the Berkeley-Darfur Stove Tested under Laboratory Conditions

Abstract: Cooking in the developing world generates pollutants that endanger the health of billions of people and contribute to climate change. This study quantified pollutants emitted when cooking with a three-stone fire (TSF) and the Berkeley-Darfur Stove (BDS), the latter of which encloses the fire to increase fuel efficiency. The stoves were operated at the Lawrence Berkeley National Laboratory testing facility with a narrow range of fuel feed rates to minimize performance variability. Fast (1 Hz) measurements of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 35 publications
5
52
1
Order By: Relevance
“…Intervention stove emissions had significantly lower AAE (group mean ~0.9) than those from traditional stoves (group means ranged from 1.2 to 1.3), which were not significantly different across seasons and groups. Preble et al also observed lower AAE values for another rocket stove model than for a three stone fire in laboratory testing [ Preble et al , ]; the rocket stove emissions in that study also had higher EC/PM ratios. These AAE values suggest that brown carbon likely makes a relatively small contribution to absorption for most emissions from cookstoves, and especially those from alternative stoves.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…Intervention stove emissions had significantly lower AAE (group mean ~0.9) than those from traditional stoves (group means ranged from 1.2 to 1.3), which were not significantly different across seasons and groups. Preble et al also observed lower AAE values for another rocket stove model than for a three stone fire in laboratory testing [ Preble et al , ]; the rocket stove emissions in that study also had higher EC/PM ratios. These AAE values suggest that brown carbon likely makes a relatively small contribution to absorption for most emissions from cookstoves, and especially those from alternative stoves.…”
Section: Resultsmentioning
confidence: 54%
“…Our results suggest that rocket stoves such as that tested here are not an effective means to reduce BC emissions and mitigate climate forcing from these short‐lived species (though they may provide other benefits including fuel use reductions). Other lab [ MacCarty et al , ; Preble et al , ; Arora and Jain , ] and field [ Roden et al , ; Johnson et al , ; Kar et al , ] studies have also observed greater absolute or relative contributions from EC/BC to PM emissions from natural draft stoves, and so this finding should not be especially surprising at this point. Intervention stoves had significantly higher EC EFs, and EC contributions to PM, than traditional stoves, and thus light absorption from aerosols will be greater and the potential offsets from cooling OC lower.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Previous studies and measurement parameters used to conduct meta-analysis of emissions by cookstove type. With the exceptions of Roden (2006) [17] Johnson (2007) [53] and Preble (2014) [42] every study conducts three tests per stove. We aggregate data from all stoves of the same class: traditional, or unimproved (T), charcoal (C), natural draft (ND), forced draft (FD), and gasifier.…”
Section: Resampling Calculationsmentioning
confidence: 99%
“…4 Researchers have explored new environmental technologies for increasing efficiency in biomass cookstoves while decreasing harmful emissions, primarily focusing on particulate matter (PM). [5][6][7][8][9][10][11] Previous research reveals that introducing turbulence (via air injection) into the gas-phase combustion zone can dramatically improve cooking performance and reduce the total mass of PM generated from biomass combustion. 5,9,11 Injecting air into the gas-phase combustion zone to generate turbulence (here-on referred to as air injection) promotes better gaseous fuel-air mixing, leading to more complete combustion, and can increase residence time of soot in the flame, promoting oxidation of soot.…”
Section: Introductionmentioning
confidence: 99%